1996
DOI: 10.1089/jir.1996.16.151
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bed Rest and Head-Down Tilt to Simulate Spaceflight-Induced Immune System Changes

Abstract: Bed rest, both with and without head-down tilt, has been extensively used as an earth-bound analog to study physiologic effects mimicking those occurring in weightlessness during spaceflight. We have been able to show in six subjects that 4 weeks of head-down tilt bed rest induces a significant decrease in interleukin-2 secretion by PHA-stimulated T lymphocytes. Another study, lasting 113 days, with two subjects showed a decreased interleukin-2 receptor expression in PHA-stimulated peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
3
17
2
Order By: Relevance
“…It seems that bed rest leads to an increase in proinflammatory cytokine secretion as shown during a 113-day HDT bed rest study (Schmitt et al 1996). Time-course measurements, however, are not available in this experiment.…”
Section: Inflammatory Processesmentioning
confidence: 76%
“…It seems that bed rest leads to an increase in proinflammatory cytokine secretion as shown during a 113-day HDT bed rest study (Schmitt et al 1996). Time-course measurements, however, are not available in this experiment.…”
Section: Inflammatory Processesmentioning
confidence: 76%
“…Previous studies have demonstrated that natural killer (NK) cells were seen to decrease in number. 10,12,19 The number and proliferation of lymphocytes has been shown to decrease in bed rest. 19,30 CD3 1 T cells and monocytes indicated a decreased level in bed rest.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous experimental conditions, mainly confinement [9,20,28,30] and head-down tilt bed rest (HDT) [7,12,17,23], have been undertaken in order to differentiate and identify various spaceflight-related factors influencing the immune system. HDT reproduces many of the physiological changes observed in space, such as redistribution of body fluids and cardiovascular deconditioning [2,26], bone demineralization [15,31] and muscle atrophy [6], after several days or weeks.…”
Section: Introductionmentioning
confidence: 99%
“…It seems likely altered immune function plays an important role in the origin of these diseases. In a previous study we showed that immediately after a 4-week HDT, a significant decrease of interleukin-2 (IL-2) secretion by T-lymphocytes occurred in response to low doses of phytohaemagglutinin-P (PHA), whilst an increase in IL-1 secretion was observed during a 119-day-period of HDT [23]. Experiments with anti-orthostatically suspended rodents showed that in vitro immune disturbances occur as well, such as a decrease in interferon-α/β production [4], and in vivo immune changes such as greater sensitivity to viral infection [19].…”
Section: Introductionmentioning
confidence: 99%